Mechanisms by Which Different Functional States of Mitochondria Define Yeast Longevity - Beach, Adam (Int J Mol Sci, 2015)
Mitochondrial functionality is vital to organismal physiology. A body of evidence supports the notion that an age-related progressive decline in mitochondrial function is a hallmark of cellular and organismal aging in evolutionarily distant eukaryotes. Studies of the baker’s yeast Saccharomyces cerevisiae, a unicellular eukaryote, have led to discoveries of genes, signaling pathways and chemical compounds that modulate longevity-defining cellular processes in eukaryotic organisms across phyla. These studies have provided deep insights into mechanistic links that exist between different traits of mitochondrial functionality and cellular aging. The molecular mechanisms underlying the essential role of mitochondria as signaling organelles in yeast aging have begun to emerge. In this review, we discuss recent progress in understanding mechanisms by which different functional states of mitochondria define yeast longevity, outline the most important unanswered questions and suggest directions for future research.